Postscript - Sarah Whatley (The International Journal of Screendance, 2016)
An issue of a journal that focuses on just one art work may be unusual, but the range and the breadth of the perspectives adopted by all the authors included here demonstrate that there is much to appreciate in this single work. Such attention given to All This Can Happen (ATCH) might also suggest that, as editors of this issue, we regard it as a landmark screendance work, and in many ways it is. It arrived at a time when changes were taking place in the art world. ATCH reflects, or perhaps contributed to, some of these changes, including: that of the shifting relationship between dance and visual arts that has subsequently posed a challenge to established hierarchies, the fascination with early technologies as source material in the production of new art work, and a growing interest in reconnecting with the past through reusing and reimagining archival content.